Annual cycle of the mexican ground squirrel (Xerospermophilus perotensis) - Montero Bagatella, Sandra Helena; González-Romero, Alberto; Sánchez-Rojas, Gerardo; Gallina, Sonia (THERYA, 2018)
Seasonality and changes in climate and habitat dynamics lead ground squirrels to use resources during the most favorable seasons and avoid less favorable conditions by hibernating. The Perote ground squirrel (Xerospermophilus perotensis) is nationally and internationally classified as vulnerable to extinction; however, our knowledge of this species is scant. The aim of this study was to describe and analyze its annual cycle. Temperature and rainfall data (2008 to 2014) for the area were used. Animal frequencies were obtained for seven sites by capture-mark-recapture; captured animals were marked, and their sex, weight, age and reproductive status noted. Population structure was obtained for each site using the male:female sex ratio and age structure. Activity during the annual cycle is statistically associated with temperature. Scrotal males were most abundant while females with signs of pregnancy and those lactating were recorded least often. The number of adults and juveniles differed statistically, with adults more abundant throughout the study. Weight varied throughout the study, and differed between adults and juveniles. The Perote ground squirrel exhibits phenological patterns similar to those of species of the genus Spermophilus, which respond to changes in temperature and its activity cycle begins in spring and ends in autumn. The weight of the squirrels was dynamic, probably resulting from reproduction, hibernation and their response to changes in environmental resources. The frequency of this species was low, with few juveniles recorded, indicating that X. perotensis is facing serious problems, likely from severe anthropogenic pressure and its own ecological characteristics.